Is basic science falling behind? A mixed methods study of bibliometric data and expert interviews in the field of cardiovascular research. (25th November 2020) - Lichtenauer, M
Abstract: Introduction: Scientists in the field of cardiovascular research face many difficulties today and find themselves under considerable pressure to be successful with their projects and publish their results on a regular basis (the publish or perish aphorism). Purpose: The objective of this mixed methods study that included quantitative and qualitative research methods was to analyse prospects of scientific success and how scientists see opportunities, risks and how they try to adapt to the current publication system. Methods: An analysis of all publications that were published by our department in the years 2014–2019 (total of 104 publications) was performed. Publications were allocated to the sub-categories basic science, clinical science, register studies/database studies and others (letters, reviews, editorials). Further specific characteristics (impact factor, number of authors/institutions, utilization of an animal model and project costs) were also collected. Furthermore, a total of 14 interviews with experts in the field of cardiovascular research were conducted. Interviews were recorded and transcribed. For quantitative text analysis MaxQDA software and the method proposed by Philipp Mayring was used. Results: When analysing the publication output of our department we found that achieved impact factors points were equally distributed between basic science, clinical science and register/database studies. Project costs were considerable higher for basic science studies compared to clinical studies and even more to register/database studies (p=0.0001). A correlation between costs and impact factor was found for basic science studies only (r=0.66, p=0.004). A multivariable regression analysis showed that project costs, number of authors and the use of an animal model, but not the number of institutions, was associated with a higher impact factor. Experts in the field shared the opinion that it might be "easier" to be successful with clinical science studies as they require less resources such as grant money, personnel and technical equipment. Moreover, upcoming risks such as competition for grant money, pressure to publish results, inadequacy of the impact factor system, securing ones job, rising publication costs and more pressure of time due to patient care, research and teaching duties for academic personnel were also highlighted to worsen the situation. Conclusion: Based on own data and the views of experts it seems much more effort- and cost-efficient to pursue projects in clinical science. Researchers in the current academic system are pressured by multiple risks. After interpretation of the obtained quantitative and qualitative material, one could hypothesize that it might be easier to be successful with focussing on clinical studies when starting ones research career. These data give support to the concerns that the field of basic science might fall behind and less young scientists would opt for a career path in this field. Funding Acknowledgement: Type of funding source: None